KESESUAIAN UKURAN BEBERAPA BAGIAN KONSTRUKSI KAPAL IKAN DI PPI MUARA ANGKE JAKARTA UTARA DENGAN ATURAN BIRO KLASIFIKASI INDONESIA - Bramantyas Febriyansyah; Mohammad Imron; Budhi H. Iskandar (Buletin PSP, 2009)
The purpose of this research is to know dimension size of some construction parts of fishing boat in Muara Angke Fishing Landing Port (PPI Muara Angke, North Jakarta) and to know its compliment to the rule of Indonesian Classification Beareau (BKI).  The method of case study and simple statistic are applied in this research.  The result shows that from 17 (seventeen) samples of fishing boat mostly do not comply with the BKI rules.  Boat builder mostly used their own method that has given from previous generation to build a boat compare to using BKI rules as standard.Key words: compliment, dimension size, fishing boat construction